Protein kinase Cε regulates nuclear translocation of extracellular signal-regulated kinase, which contributes to bradykinin-induced cyclooxygenase-2 expression - Nakano, Rei (Sci Rep, 2018)
The proinflammatory mediator bradykinin stimulated cyclooxygenase-2 (COX-2) expression and subsequently prostaglandin E(2) synthesis in dermal fibroblasts. The involvement of B2 receptors and Gαq in the role of bradykinin was suggested by using pharmacological inhibitors. The PKC activator PMA stimulated COX-2 mRNA expression. Bradykinin failed to induce COX-2 mRNA expression in the presence of PKC inhibitors, whereas the effect of bradykinin was observed in the absence of extracellular Ca(2+). Bradykinin-induced COX-2 mRNA expression was inhibited in cells transfected with PKCε siRNA. These observations suggest that the novel PKCε is concerned with bradykinin-induced COX-2 expression. Bradykinin-induced PKCε phosphorylation and COX-2 mRNA expression were inhibited by an inhibitor of 3-phosphoinositide-dependent protein kinase-1 (PDK-1), and bradykinin-induced PDK-1 phosphorylation was inhibited by phospholipase D (PLD) inhibitors, suggesting that PLD/PDK-1 pathway contributes to bradykinin-induced PKCε activation. Pharmacological and knockdown studies suggest that the extracellular signal-regulated kinase 1 (ERK1) MAPK signaling is involved in bradykinin-induced COX-2 expression. Bradykinin-induced ERK phosphorylation was attenuated in the cells pretreated with PKC inhibitors or transfected with PKCε siRNA. We observed the interaction between PKCε and ERK by co-immunoprecipitation experiments. These observations suggest that PKCε activation contributes to the regulation of ERK1 activation. Bradykinin stimulated the accumulation of phosphorylated ERK in the nuclear fraction, that was inhibited in the cells treated with PKC inhibitors or transfected with PKCε siRNA. Consequently, we concluded that bradykinin activates PKCε via the PLD/PDK-1 pathway, which subsequently induces activation and translocation of ERK1 into the nucleus, and contributes to COX-2 expression for prostaglandin E(2) synthesis in dermal fibroblasts.